2021
DOI: 10.1113/jp282281
|View full text |Cite
|
Sign up to set email alerts
|

GLOBAL REACH 2018: intra‐arterial vitamin C improves endothelial‐dependent vasodilatory function in humans at high altitude

Abstract: High altitude‐induced hypoxaemia is often associated with peripheral vascular dysfunction. However, the basic mechanism(s) underlying high‐altitude vascular impairments remains unclear. This study tested the hypothesis that oxidative stress contributes to the impairments in endothelial function during early acclimatization to high altitude. Ten young healthy lowlanders were tested at sea level (344 m) and following 4–6 days at high altitude (4300 m). Vascular endothelial function was determined using the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The study by Stone et al . (2022) demonstrates impaired endothelial vascular reactivity at high altitudes, the extent of which is determined by the level of hypoxaemia, identifying oxidative stress as a contributing factor to vascular dysfunction. The near reversal of vasodilatory impairment by vitamin C infusion suggests antioxidant supplementation as a means of reducing vascular dysfunction associated with high‐altitude acclimatization, a process that can lead to hypoxia‐related complications.…”
Section: Figure Effect Of Ach and Vitamin C On The Endothelial‐depend...mentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Stone et al . (2022) demonstrates impaired endothelial vascular reactivity at high altitudes, the extent of which is determined by the level of hypoxaemia, identifying oxidative stress as a contributing factor to vascular dysfunction. The near reversal of vasodilatory impairment by vitamin C infusion suggests antioxidant supplementation as a means of reducing vascular dysfunction associated with high‐altitude acclimatization, a process that can lead to hypoxia‐related complications.…”
Section: Figure Effect Of Ach and Vitamin C On The Endothelial‐depend...mentioning
confidence: 99%
“…This observed difference could be a result of increased oxidative stress on the endothelium, such as seen in metabolic syndrome, although this link has not been investigated in hypobaric hypoxia. As such, in a recent study published in the Journal of Physiology, Stone et al (2022) investigated the mechanism of oxidative stress on endothelial-dependent vasodilatory dysfunction during short-term acclimatization to high altitude. The vascular function of 10 healthy lowlanders in response to ACh, SNP, and ACh + Vitamin C (VitC) was measured at sea level (344 m) and again 4-6 days after rapid ascent to 4300 m elevation via a vehicle in 8 h. Stone et al (2022) quantified vascular function using the gold standard, strain-gauge venous occlusion plethysmography technique to measure arterial forearm blood flow (FBF) following the infusion of endothelial agonists.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By 4–6 days at 4300 m, there was development of decreased hyperaemia mediated by acetylcholine, but not by SNP, and this was abrogated by local intra‐arterial vitamin C infusion in five of the 10 subjects, with little change in three, and a paradoxical fall in two, suggesting a considerable bidirectional range of responses (Figure 3 in Stone et al . 2022). Part of this heterogeneity may be related to the subject's degree of hypoxaemia, because they found a large effect on the degree of individual arterial oxygen desaturation and forearm blood flow increase to acetylcholine, with those most desaturated demonstrating the least increase with acetylcholine and conversely the greatest effect of vitamin C to induce more blood flow.…”
mentioning
confidence: 99%
“…Part of this heterogeneity may be related to the subject's degree of hypoxaemia, because they found a large effect on the degree of individual arterial oxygen desaturation and forearm blood flow increase to acetylcholine, with those most desaturated demonstrating the least increase with acetylcholine and conversely the greatest effect of vitamin C to induce more blood flow. In Figure 4 of Stone et al (2022), it would have been interesting to have each subject identified for how vitamin C altered their FMD with acetylcholine. The authors show impaired vascular endothelial cell-mediated hyperaemia by hypoxia after 4-6 days, which is evident even with acute hypoxaemia of half an hour and sustained in subjects studied after 3 weeks in other work by this group.…”
mentioning
confidence: 99%